Transportation Collaboration Strategy in Export and Import Operations to Reduce Carbon Emissions: A Case Study of PT. XYZ - Budi Setiawan; Adi Budipriyanto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This thesis discusses transportation collaboration strategies in export and import activities at PT. XYZ to reduce carbon emissions. The research aims to identify efficient shipping methods that can minimize environmental impact. Through an analysis of various collaboration schemes, this study evaluates the comparison of carbon emissions produced from collaborative and non collaborative shipping. The research findings indicate that non-collaborative shipping generates approximately 1,680,102,896 tons of carbon emissions annually, whereas collaborative shipping has successfully reduced emissions to 699,743tons per year, achieving a total reduction of 58%. The implementation of collaboration strategies not only positively impacts emission reduction but also provides financial benefits to the company, with transportation cost savings of up to 15%. These findings are expected to serve as a reference for the development of green policies in the transportation and logistics industry.